Functional super-hydrophobic quartz sand with MOF structure as well as preparation method and application of functional super-hydrophobic quartz sand
By superhydrophobic modification of quartz sand and composited with ZIF-8 material, functional superhydrophobic quartz sand with MOF structure is formed, which solves the problems of low removal efficiency of microplastics and difficulty in regeneration of adsorbents in the prior art, and achieves efficient removal of microplastics in rainwater runoff and reusable materials.
Patent Information
- Application Number
- CN202510096433.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art is difficult to effectively remove microplastics in stormwater runoff and sewage, and existing adsorbents have many challenges in regeneration and preventing secondary release of microplastics.
By superhydrophobic modification of quartz sand and composited with ZIF-8 material, functional superhydrophobic quartz sand with MOF structure is formed, increasing the hydrophobic strength and range of microplastics and filter materials, thereby improving the adhesion efficiency and removal performance of microplastics.
It has achieved efficient removal of microplastics in rainwater runoff, with a removal rate of 98.3%. The material preparation process is simple and it is not easy to produce secondary pollution. It is suitable for large-scale water treatment applications.
Smart Images

Figure CN119909656A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rainwater runoff and sewage microplastic pollution control and treatment, and in particular to a functional super-hydrophobic quartz sand with an MOF structure, and a preparation method and application thereof. Background Art
[0002] Microplastics (plastic fragments with a particle size of less than 5mm) exist in large quantities in rivers, lakes and oceans around the world, and are most abundant in densely populated urban waters. Microplastics are persistent in the aquatic environment and harmful to the aquatic ecology, posing a threat to aquatic life; they can also invade the human brain, heart, placenta and blood system, causing cardiovascular disease and nervous system damage; microplastics can even affect the transfer of resistance genes and have toxic effects on microbial populations. Urban rainwater runoff is the main way for microplastics to enter water bodies, and preventing the migration of microplastics from urban rainwater runoff to water bodies is an urgent problem that needs to be solved.
[0003] At present, the control methods of microplastics in water environment can be summarized into three categories: physical removal, biological removal and chemical degradation. Among them, physical removal includes adsorption, coagulation, membrane filtration, and chemical degradation methods include advanced oxidation process and photocatalysis. Coagulation has a high microplastic separation efficiency, but the regeneration of coagulants and adsorbents will cause microplastics to be released into the environment again. Compared with coagulation and adsorption, membrane filtration has a higher removal efficiency for microplastics, but in practical applications, attention should be paid to membrane pollution and loss, and the management and maintenance costs are high. Advanced oxidation, photocatalysis and other methods can degrade and transform microplastics and plastic waste, but the safety of degradation products is highly controversial. The biological degradation cycle is long and the degradation efficiency is low, and it is impossible to achieve efficient removal of microplastics in a short time. In general, physical treatment technology, especially adsorption, is relatively mature and has a high microplastic removal rate. It is the only choice with great application prospects and eco-friendly for the control and management of microplastics in water bodies.
[0004] In recent years, many researchers have studied the removal of microplastics using a variety of adsorbents such as biochar, activated carbon, sponges, carbon nanotubes, aerogels, and metal organic frameworks. Studies have shown that there is a certain affinity between carbon materials and microplastics. Carbon materials can interact with microplastics in water through a series of effects such as functional groups and "stuck", "trapped" and "entangled", so that microplastics are fixed by carbon material particles and even retained in the pore structure of carbon materials, with excellent removal performance. However, there are many challenges in the regeneration of adsorbents and the prevention of secondary release of microplastics. Metal organic frameworks (MOFs) are porous crystalline materials assembled from metal ions and organic ligands, which have attracted widespread research interest in various applications such as gas storage, catalysis, separation, sensing and water treatment. Due to their high porosity, designable structure and rich functions, they have gradually become an ideal choice for microplastic removal. However, MOF materials generally have the characteristics of poor processing performance, fragility, difficulty in recycling and separation, and they are sensitive to moisture and acid and unstable in aqueous media, which limits their practical application. The former can be solved by loading MOF materials onto suitable supporting materials or frames. Sponges and aerogels are common carriers, but there has been no research on using quartz sand as a carrier for MOF materials. In addition, the above materials have relatively simple forms and application scenarios for removing microplastics, and can usually only be used as adsorbents on a laboratory scale.
[0005] Therefore, it is necessary to develop an efficient, economical, practical and reusable adsorbent to achieve efficient removal of microplastics in rainwater runoff and sewage. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a functional superhydrophobic quartz sand with a MOF structure to achieve efficient removal of microplastics in rainwater runoff.
[0007] As a natural filter material, quartz sand is highly favored for its economy, easy modification and flexible use. It can not only be used as a carrier of MOF, but also improve the adsorption of microplastics by changing its roughness and wettability. The successfully constructed superhydrophobic quartz sand can not only be used as an adsorbent at a laboratory scale, but also as a filler in green facilities such as artificial wetlands, bioretention facilities, and rain gardens to enhance the removal of microplastics in rainwater runoff. The interaction force between microplastics and filter media is equal to the sum of electrostatic force, van der Waals force and hydrophobic force. This theory is widely used to explain the migration and deposition behavior of particles in porous media. The range of hydrophobic force can reach 100nm, which is much longer than van der Waals force, so it is often called long-range adsorption force, and the strength of hydrophobic force is much greater than the other two forces. The strength and range of hydrophobic interaction between particles increase with the increase of contact angle, and the hydrophobic effect is more significant when the contact angle is greater than 90°. Among MOF materials, zeolite imidazolate framework materials (ZIF) are easy to prepare and have a large specific surface area, a stable structure and a large adsorption capacity, and have broad prospects in pollutant treatment. In view of the above considerations and based on the hydrophobic characteristics of microplastics, the present invention proposes to modify quartz sand to be super-hydrophobic and composite it with ZIF materials to give it adsorption characteristics, thereby increasing the hydrophobic interaction strength and range of microplastics and filter materials to increase the adhesion efficiency of microplastics on the surface of quartz sand and enhance the removal performance of microplastics.
[0008] Specifically, the present invention provides a functional super-hydrophobic quartz sand with a MOF structure, which is assembled layer by layer from hexadecyltrimethoxysilane HDTMS, ZIF-8 and polydopamine PDA. The HDTMS layer gives the material super-hydrophobicity, the ZIF-8 layer provides a high specific surface area and a large adsorption capacity, and the PDA layer acts as a bridging layer to enhance the structural stability and chemical functionality of the material. Since microplastics are hydrophobic, the composite material achieves effective adsorption of microplastics through a multi-layer assembly structure on the surface, mainly through hydrophobic forces, van der Waals forces, electrostatic effects, P-π conjugation, and hydrogen bonds, to achieve efficient removal of common microplastics in rainwater runoff such as polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET).
[0009] The present invention also provides a method for preparing functional super-hydrophobic quartz sand having a MOF structure, comprising the following steps:
[0010] Step SS1, pretreatment of quartz sand:
[0011] The quartz sand with a particle size of 0.15-0.18 mm was washed with tap water, 5% HNO3, 5% NaOH and deionized water in turn, and dried for later use;
[0012] Step SS2, preparation of PDA@QS:
[0013] A certain amount of dopamine hydrochloride is weighed and dissolved in a Tris-HCl buffer solution with a pH of 8.5 to obtain a dopamine hydrochloride solution; the quartz sand pretreated in step SS1 is immersed in the dopamine hydrochloride solution and continuously stirred at room temperature for 12 to 24 hours to form a polydopamine (PDA) coating on the quartz sand through self-polymerization of dopamine hydrochloride DA·HCl molecules to enhance its adhesion, and PDA@QS is obtained after drying;
[0014] Step SS3, preparation of ZIF-8@PDA@QS:
[0015] Zinc nitrate hexahydrate and 2-methylimidazole were dissolved in methanol to obtain solution A and solution B, respectively. PDA@QS prepared in step SS2 was added to solution A and stirred at room temperature for 15 min at a stirring speed of 800-1500 r / min. Solution B was then poured into the above system to allow ZIF-8 to grow in situ on PDA@QS. ZIF-8@PDA@QS was obtained after drying.
[0016] Step SS4, preparation of HDTMS@ZIF-8@PDA@QS:
[0017] In order to give ZIF-8@PDA@QS superhydrophobicity, it was modified with hexadecyltrimethoxysilane (HDTMS); the ZIF-8@PDA@QS prepared in step SS3 was immersed in a 10% vol HDTMS-ethanol solution, sealed and stirred at room temperature for 3 hours, and HDTMS@ZIF-8@PDA@QS was obtained after drying. HDTMS@ZIF-8@PDA@QS is a functional superhydrophobic quartz sand with a MOF structure.
[0018] Furthermore, in step SS1, the ratio of the volume mL of tap water, 5% HNO3, 5% NaOH and deionized water to the mass g of quartz sand is 2 to 5:1.
[0019] Further, in step SS1, the quartz sand is washed with tap water, 5% HNO3, 5% NaOH and deionized water for 3 to 5 times respectively, the drying temperature is 60 to 80°C, and the drying time is 6 to 12 hours;
[0020] Furthermore, in step SS2, the volume mL of Tris-HCl buffer is 300 to 600 times the mass of dopamine hydrochloride g, the ratio of the volume mL of dopamine hydrochloride solution to the mass g of quartz sand is 2:1 to 5:1, the drying temperature is 60 to 80°C, and the drying time is 8 to 12 h.
[0021] Furthermore, in step SS3, the ratio of the volume mL of methanol to the mass g of zinc nitrate hexahydrate is 8 to 12:1:1, the ratio of the volume mL of methanol to the mass g of 2-methylimidazole is 7 to 11:1, and the molar ratio of solution A to solution B is 1:4 to 1:8.
[0022] Furthermore, in step SS3, the in-situ growth temperature is 50-70° C., and the time is 30-60 min; the drying temperature is 60-80° C., and the drying time is 8-12 h.
[0023] Furthermore, in step SS4, the stirring speed is 150-200 r / min, the drying temperature is 60-80° C., and the drying time is 12-24 h.
[0024] Furthermore, the volume mL of the 10% volHDTMS-ethanol solution in step SS4 is 1 to 3 times the mass g of ZIF-8@PDA@QS.
[0025] The present invention also provides an application of the functional super-hydrophobic quartz sand with a MOF structure as described above, wherein the functional super-hydrophobic quartz sand with a MOF structure is used to remove microplastics in rainwater runoff, specifically, a certain amount of HDTMS@ZIF-8@PDA@QS is weighed in an iodine volumetric flask, a certain volume of microplastic suspension is transferred therein, the concentration of the microplastic suspension is 5 to 10:1 to the concentration of the adsorbent, and the suspension is placed in an air bath constant temperature oscillator, and oscillated at an oscillation rate of 180r / min for 120min at room temperature to achieve adsorption equilibrium. The concentration of PP, PE, and PET microplastic suspensions is prepared according to the actual concentration of microplastics in rainwater runoff.
[0026] Compared with the existing technology, the functional super-hydrophobic quartz sand with MOF structure and its preparation method and application of the present invention have the following significant beneficial effects:
[0027] 1. The present invention is to modify quartz sand to be super-hydrophobic, and ZIF-8 is strongly integrated on the surface of quartz sand, prepare a functional super-hydrophobic quartz sand with a metal organic framework, obtain a composite material combining two component characteristics, not only give quartz sand based on the porous adsorption characteristics of MOF materials, and change it from hydrophilicity to super-hydrophobicity, improve the removal efficiency of microplastics. The composite material can produce a strong hydrophobic force and strengthen adsorption with different types of microplastics under various environmental conditions. The material preparation process is simple, is not easy to produce secondary pollution, is suitable for large-scale water treatment applications, and provides a new idea for controlling microplastics in rainwater runoff and sewage.
[0028] 2. The adsorption performance of PDA@QS, ZIF-8@PDA@QS and HDTMS@ZIF-8@PDA@QS materials for polypropylene (PP) microplastics gradually improved at different modification stages, with removal rates of 44.6%, 63.2% and 98.3%, respectively, and the adsorption amount increased to 66.7 mg / g accordingly. The removal rates of HDTMS@ZIF-8@PDA@QS for polyethylene (PE) and polyethylene terephthalate (PET) microplastics reached 97.1% and 85.5%, respectively, showing a wide range of adsorption adaptability.
[0029] 3. FTIR, XPS and XRD confirmed that the gradual introduction of PDA and ZIF-8 formed abundant functional groups (such as phenolic hydroxyl, amine and imidazole ring) on the surface of the material, which enhanced the chemical adsorption of microplastics; HDTMS modification significantly increased the hydrophobicity of the material, making it more suitable for adsorbing hydrophobic microplastics. SEM and EDS characterization showed that the uniform coverage of ZIF-8 and HDTMS layers made the surface rougher and had a nanoscale MOF structure, increasing the specific surface area and active sites. The contact angle test showed that the surface of the material modified with HDTMS had superhydrophobic properties, which strengthened the interaction with hydrophobic microplastics.
[0030] 4. The effective adsorption of microplastics by HDTMS@ZIF-8@PDA@QS is the result of the combined effects of hydrophobic forces, van der Waals forces, electrostatic effects, P-π conjugation, hydrogen bonds, etc. It is feasible to use the functional superhydrophobic quartz sand with MOF structure prepared by the present invention as an adsorbent or as a filler in bioretention facilities to remove microplastics in rainwater runoff. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Water contact angle diagrams of QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS prepared in Example 1: QS is 1 (a), PDA@QS is 1 (b), ZIF-8@PDA@QS is 1 (c), and HDTMS@ZIF-8@PDA@QS is 1 (d).
[0032] Figure 2 2(a) and 2(b) are scanning electron microscope images of the material prepared in Example 1 at different magnifications, 2(c), 2(d), and 2(e) are scanning electron microscope images of HDTMS@ZIF-8@PDA@QS at different magnifications, respectively.
[0033] Figure 3 is the EDS graph of the material prepared in Example 1, and 3(a) and 3(b) are the EDS graphs of QS and HDTMS@ZIF-8@PDA@QS, respectively.
[0034] Figure 4 These are the FTIR graphs of QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS prepared in Example 1.
[0035] Figure 5 These are the XRD patterns of QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS prepared in Example 1.
[0036] Figure 6 These are the XPS graphs of QS and HDTMS@ZIF-8@PDA@QS prepared in Example 1.
[0037] Figure 7 These are the TGA graphs of QS and HDTMS@ZIF-8@PDA@QS prepared in Example 1. DETAILED DESCRIPTION
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0039] The technical solution of the present invention is further explained below in conjunction with implementation cases.
[0040] Example 1
[0041] This embodiment provides a method for preparing functional super-hydrophobic quartz sand with a MOF structure, and the specific steps are as follows:
[0042] Step 1, pretreatment of quartz sand:
[0043] 25 g of quartz sand was washed three times with 100 mL of tap water, 5% HNO3, 5% NaOH and deionized water in sequence. The particle size of the quartz sand was 0.18 mm. Surface pollutants and impurities were removed and the sand was dried at 60°C for 6 h before use. The pretreated quartz sand was referred to as QS.
[0044] Step 2, preparation of PDA@QS:
[0045] Weigh 0.2g dopamine hydrochloride (DA·HCl) and dissolve it in 100mL Tris-HCl (10mM, pH=8.5) solution. Stir continuously at room temperature for 10min. The solution changes from clear to brown to obtain dopamine hydrochloride solution. Add the washed quartz sand to the dopamine solution, stir continuously at room temperature for 12h, and dry at 60℃ for 10h to obtain polydopamine-coated quartz sand PDA@QS.
[0046] Step 3, preparation of ZIF-8@PDA@QS:
[0047] 5 g of zinc nitrate hexahydrate was dissolved in 50 mL of methanol to obtain solution A; 5.5 g of 2-methylimidazole was dissolved in 50 mL of methanol to obtain solution B; 25 g of PDA@QS was added to solution A and stirred at room temperature for 15 min at a stirring speed of 1200 r / min. Solution B was then poured into the above system and stirred continuously for 1 h in a constant temperature water bath at 70 °C to allow ZIF-8 to grow in situ on PDA@QS. ZIF-8@PDA@QS was obtained after drying at 60 °C for 12 h.
[0048] Step 4, preparation of HDTMS@ZIF-8@PDA@QS:
[0049] 25 g ZIF-8@PDA@QS was immersed in 75 mL 10% HDTMS-ethanol (v:v) solution, sealed and stirred at room temperature for 3 h at a stirring speed of 1500 r / min; HDTMS@ZIF-8@PDA@QS was obtained after drying at 60°C for 24 h.
[0050] The QS, PDA@QS, ZIF-8@PDA@QS and HDTMS@ZIF-8@PDA@QS prepared in the above steps 1, 2, 3 and 4 were characterized:
[0051] 1. Use a video optical contact angle meter (OCA25, East Defei, Germany) to measure the water contact angle. Paste the prepared QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS on a glass slide with double-sided tape, take 3 μL of deionized water, drop it on any three different positions on the surface of the four quartz sands to measure the contact angle, and take the average value as the water contact angle of the four quartz sand surfaces. Figure 1 As shown, Figure 1 (a), 1(b), 1(c), and 1(d) are the water contact angle graphs of QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS, respectively.
[0052] 2. Scanning electron microscope SEM (ZEISS GeminiSEM 500, Carl Zeiss, Germany) was used to reflect the microscopic morphology of the samples. Figure 2 (a) and (b) are scanning electron microscope images of QS at 500x and 3000x magnifications. Figure 2 (c), (d), and (e) are the scanning electron micrographs of HDTMS@ZIF-8@PDA@QS at 500x, 3000x, and 30000x magnifications, respectively. EDS energy spectrum analysis reflects the elements and contents of the samples. Figure 3 (a) and 3(b) are the EDS images of QS and HDTMS@ZIF-8@PDA@QS.
[0053] 3. Fourier transform infrared spectroscopy (FTIR) (VERTEX 70, Bruker, Germany) was used at a wavelength of 400-4000cm -1 The surface functional groups of the samples were detected within a certain range, and the samples were scanned by X-ray diffraction (XRD) (D8ADVANCE, Bruker, Germany) at a scanning speed of 10° / min within a 2θ range of 5-90° to identify the content and structure of each component. Figure 4 FTIR graphs of QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS. Figure 5 XRD patterns of QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS.
[0054] 4. X-ray electron spectroscopy (XPS) (ESCALAB 250Xi, Thermo Fisher Scientific Inc., USA) was used to measure the electron cloud distribution and energy level structure on the sample surface. Figure 6 XPS graphs of QS and HDTMS@ZIF-8@PDA@QS.
[0055] 5. A thermogravimetric analyzer (TGA55, TA Instruments, USA) was used at 100 mL / min N 2 In a flowing atmosphere, 8 mg of sample was subjected to thermogravimetric analysis at 30-800°C. Figure 7 TGA diagrams of QS and HDTMS@ZIF-8@PDA@QS.
[0056] Characterization results: Figure 1 The water contact angles of QS, PDA@QS, ZIF-8@PDA@QS, and HDTMS@ZIF-8@PDA@QS are 0°, 73°, 84°, and 164°, respectively, indicating that the original quartz sand is hydrophilic, and the final product after layer-by-layer assembly is superhydrophobic, proving the successful grafting of HDTMS. Figure 2 It can be seen that Figure 2(a) and Figure 2 (b) Compared with the original quartz sand, the surface of the modified HDTMS@ZIF-8@PDA@QS is rougher. Figure 2 (c) Figure 2 (d) Figure 2 As shown in (e), a large number of ZIF-8 nanoparticles with regular dodecahedral structures are attached to the surface, indicating that ZIF-8 is successfully assembled on the quartz sand surface. Figure 3 It shows that in addition to the inherent elements Si and O of quartz sand, the modified elements such as C, N, and Zn are evenly coated on the surface of quartz sand, indicating the successful assembly of PDA, ZIF-8, and HDTMS. Figure 4 It can be seen that compared with QS, the infrared spectrum of HDTMS@ZIF-8@PDA@QS is at 2920 cm -1 、2948cm -1 、1960cm -1 、1073cm -1 、1023cm -1 New absorption peaks appeared at , corresponding to the stretching vibrations of -CH3, -CH2 in HDTMS, C-O in PDA, and C=N, C-N in the imidazole ring, further illustrating the successful grafting of PDA, ZIF-8 and HDTMS, which is consistent with the EDS results. Figure 5 It was shown that HDTMS@ZIF-8@PDA@QS and original quartz sand presented similar characteristic diffraction peaks, indicating that PDA, ZIF-8 and HDTMS were successfully synthesized on the surface of quartz sand, and the inherent structure of quartz sand was retained during the modification process. Figure 6 The measurement results are consistent with the EDS results, indicating that elements such as C, N, and Zn are evenly coated on the surface of quartz sand. Figure 7 The results reflect the thermal stability of HDTMS@ZIF-8@PDA@QS and QS. The results show that HDTMS@ZIF-8@PDA@QS has good thermal stability and only loses 6% of its mass during the heating process. The above characterization results all prove that HDTMS, ZIF-8 and polydopamine PDA are successfully assembled on the surface of quartz sand, which has both MOF structure and superhydrophobic properties.
[0057] Example 2
[0058] This embodiment provides an application of PDA@QS. The preparation of PDA@QS refers to step 1 and step 2 of Example 1. Specific application steps: add 0.3g PDA@QS to an iodine volume flask containing 20ml1g / L PP microplastic (particle size 25um) suspension, place it in an air bath constant temperature oscillator, and oscillate at an oscillation rate of 180r / min for 120min at a temperature of 25°C to reach adsorption equilibrium. After the adsorption is completed, let it stand for 15min. Due to its high density, PDA@QS settles to the bottom by gravity. The supernatant is taken to measure the turbidity of microplastics, and the microplastic removal rate is calculated. The removal rate of PP microplastics is calculated to be 44.6%.
[0059] The method for detecting the concentration of microplastics is as follows: take 15 mL of supernatant, place it in a sample bottle, shake it well, and use a 2100Q turbidity meter (Hach Company, USA) to measure the turbidity of the remaining microplastics in the supernatant after adsorption. The turbidity is measured to indirectly reflect the concentration of microplastics. The method used to calculate the removal rate and adsorption amount of PP, PE, and PET is as follows:
[0060]
[0061] Where: η is the removal rate of PP, PE, and PET by the adsorbent (%);
[0062] q e is the adsorption amount of PP, PE and PET by the adsorbent (mg / g);
[0063] C0 is the initial concentration of PP, PE, and PET (mg / L);
[0064] C e is the residual concentration of PP, PE, and PET in the solution after adsorption (mg / L);
[0065] V is the volume of the reaction solution (L);
[0066] m is the mass of the adsorbent (g).
[0067] Example 3
[0068] This embodiment provides an application of ZIF-8@PDA@QS. The preparation of ZIF-8@PDA@QS refers to step 1, step 2 and step 3 of Example 1. Specific application steps: add 0.3g ZIF-8@PDA@QS to an iodine volume flask containing 20ml1g / L PP microplastic (particle size 25um) suspension, place it in an air bath constant temperature oscillator, and oscillate at an oscillation rate of 180r / min for 120min at a temperature of 25°C to reach adsorption equilibrium. After the adsorption is completed, let it stand for 15min. ZIF-8@PDA@QS settles to the bottom by gravity due to its high density. Take the supernatant to measure the turbidity of microplastics, and then calculate the microplastic removal rate. The removal rate of PP microplastics is calculated to be 63.2%.
[0069] Example 4
[0070] This embodiment provides an application of HDTMS@ZIF-8@PDA@QS. The preparation of HDTMS@ZIF-8@PDA@QS refers to step 1, step 2, step 3 and step 4 of Example 1. Specific application steps: add 0.3g HDTMS@ZIF-8@PDA@QS to an iodine volume flask containing 20ml1g / L PP microplastic (particle size 25um) suspension, place it in an air bath constant temperature oscillator, and oscillate at an oscillation rate of 180r / min for 120min at a temperature of 25°C to reach adsorption equilibrium. After the adsorption is completed, let it stand for 15min. Due to its high density, HDTMS@ZIF-8@PDA@QS settles to the bottom by gravity. Take the supernatant to measure the turbidity of microplastics, and then calculate the microplastic removal rate. The removal rate of PP microplastics is calculated to be 98.3%.
[0071] Example 5
[0072] This example refers to Example 4, and the difference between this example and Example 4 is that 20 ml 1 g / L of PP microplastics is replaced by 20 ml 1 g / L of polyethylene (PE) microplastics and polyethylene terephthalate (PET) microplastics, respectively. The removal rates of PE and PET microplastics are calculated to be 97.1% and 85.5%, respectively.
[0073] The statistical results of the adsorption amount and removal rate of microplastics by different hydrophobic materials prepared in Example 1 and Example 5 are shown in Table 1.
[0074] Table 1
[0075]
[0076]
[0077] Example 6
[0078] This example refers to Example 4. On the basis of Example 4, in order to test the regeneration performance of HDTMS@ZIF-8@PDA@QS, the adsorbent adsorbed with PP microplastics was separated by a 100um nylon filter membrane and dried at 60°C for 24h to obtain HDTMS@ZIF-8@PDA@QS-PP. Accurately weigh 0.4g of HDTMS@ZIF-8@PDA@QS-PP in an iodine volume flask, add 20mL of ethanol as a desorption liquid, and place it in an air bath constant temperature oscillator at an oscillation rate of 180r / min and a temperature of 25°C for 120min. The regenerated HDTMS@ZIF-8@PDA@QS was dried and used again to adsorb microplastics. The adsorption conditions were the same as in Example 4. The desorption-regeneration process was repeated 5 times, and the changes in the removal rate of microplastics after the adsorbent was regenerated were recorded. It was calculated that the removal rate of PP microplastics by HDTMS@ZIF-8@PDA@QS after 5 regenerations was 88.7%.
[0079] In summary, the functional superhydrophobic quartz sand with MOF structure proposed in this patent has achieved efficient adsorption performance for microplastics after gradual coating of different functional layers (PDA, ZIF-8, HDTMS). Through experimental verification, when the functional superhydrophobic quartz sand with MOF structure is used to remove microplastics in rainwater runoff, the adsorption performance of PDA@QS, ZIF-8@PDA@QS and HDTMS@ZIF-8@PDA@QS materials for polypropylene (PP) microplastics is gradually improved at different modification stages, and the removal rates are 44.6%, 63.2% and 98.3%, respectively, and the adsorption amount is correspondingly increased to 66.7mg / g. In addition, the removal rates of HDTMS@ZIF-8@PDA@QS for polyethylene (PE) and polyethylene terephthalate (PET) microplastics reached 97.1% and 85.5%, respectively, and it still has good removal performance after 5 regenerations, showing a wide range of adsorption adaptability. FTIR, XPS and XRD confirmed that the gradual introduction of PDA and ZIF-8 formed abundant functional groups (such as phenolic hydroxyl, amine and imidazole ring) on the surface of the material, which enhanced the chemical adsorption of microplastics; HDTMS modification significantly increased the hydrophobicity of the material, making it more suitable for adsorbing hydrophobic microplastics. SEM and EDS characterization showed that the uniform coverage of ZIF-8 and HDTMS layers made the surface rougher and had a nanoscale MOF structure, increasing the specific surface area and active sites. The contact angle test showed that the surface of the material modified by HDTMS had superhydrophobic properties, which strengthened the interaction with hydrophobic microplastics. Therefore, the effective adsorption of microplastics by HDTMS@ZIF-8@PDA@QS is the result of the combined effects of hydrophobic forces, van der Waals forces, electrostatic effects, P-π conjugation, hydrogen bonds, etc. The above results all indicate that this kind of functional superhydrophobic quartz sand with MOF structure is feasible as an adsorbent or as a filler in bioretention facilities to remove microplastics in rainwater runoff.
[0080] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A functional super-hydrophobic quartz sand with a MOF structure, characterized in that: The functional quartz sand is assembled layer by layer from hexadecyltrimethoxysilane, ZIF-8 and polydopamine.
2. The method for preparing functional super-hydrophobic quartz sand with MOF structure as claimed in claim 1, characterized in that, The following steps are involved: Step SS1, pretreatment of quartz sand: The quartz sand with a particle size of 0.15-0.18 mm was washed with tap water, 5% HNO3, 5% NaOH and deionized water in turn, and dried for later use; Step SS2, preparation of PDA@QS: Weigh a certain amount of dopamine hydrochloride, dissolve it in a Tris-HCl buffer solution with a pH of 8.5, and obtain a dopamine hydrochloride solution; immerse the quartz sand pretreated in step SS1 in the dopamine hydrochloride solution, stir continuously at room temperature for 12 to 24 hours, and obtain PDA@QS after drying; Step SS3, preparation of ZIF-8@PDA@QS: Zinc nitrate hexahydrate and 2-methylimidazole were dissolved in methanol to obtain solution A and solution B, respectively. PDA@QS prepared in step SS2 was added to solution A and stirred at room temperature for 15 min at a stirring speed of 800-1500 r / min. Solution B was then poured into the above system to allow ZIF-8 to grow in situ on PDA@QS. ZIF-8@PDA@QS was obtained after drying. Step SS4, preparation of HDTMS@ZIF-8@PDA@QS: The ZIF-8@PDA@QS prepared in step SS3 was immersed in a 10% vol HDTMS-ethanol solution, sealed and stirred at room temperature for 3 h, and HDTMS@ZIF-8@PDA@QS was obtained after drying.
3. The method for preparing functional super-hydrophobic quartz sand with MOF structure according to claim 2, characterized in that, In step SS1, the ratio of the volume mL of tap water, 5% HNO3, 5% NaOH and deionized water to the mass g of quartz sand is 2 to 5:
1.
4. The method for preparing functional super-hydrophobic quartz sand with MOF structure according to claim 2, characterized in that, In step SS1, the quartz sand is washed 3 to 5 times with tap water, 5% HNO3, 5% NaOH and deionized water respectively, the drying temperature is 60 to 80°C, and the drying time is 6 to 12 hours.
5. The method for preparing functional super-hydrophobic quartz sand with MOF structure according to claim 2, characterized in that, In step SS2, the volume mL of the Tris-HCl buffer is 300 to 600 times the mass g of dopamine hydrochloride, the ratio of the volume mL of the dopamine hydrochloride solution to the mass g of quartz sand is 2:1 to 5:1, the drying temperature is 60 to 80° C., and the drying time is 8 to 12 h.
6. The method for preparing functional super-hydrophobic quartz sand with MOF structure according to claim 2, characterized in that: In step SS3, the ratio of the volume of methanol (mL) to the mass of zinc nitrate hexahydrate (g) is 8-12:1, the ratio of the volume of methanol (mL) to the mass of 2-methylimidazole (g) is 7-11:1, and the molar ratio of solution A to solution B is 1:4-1:
8.
7. The method for preparing functional super-hydrophobic quartz sand with MOF structure according to claim 2, characterized in that: In step SS3, the in-situ growth temperature is 50-70° C., and the time is 30-60 min; the drying temperature is 60-80° C., and the drying time is 8-12 h.
8. The method for preparing functional super-hydrophobic quartz sand with MOF structure according to claim 2, characterized in that: In step SS4, the stirring speed is 800-1500 r / min, the drying temperature is 60-80° C., and the drying time is 12-24 h.
9. The method for preparing functional super-hydrophobic quartz sand with MOF structure according to claim 2, characterized in that: The volume mL of the 10% volHDTMS-ethanol solution in step SS4 is 1 to 3 times the mass g of ZIF-8@PDA@QS.
10. The use of the functional super-hydrophobic quartz sand with MOF structure according to any one of claims 1 to 9, characterized in that: The functional superhydrophobic quartz sand with MOF structure is used to remove microplastics in rainwater runoff. A certain amount of HDTMS@ZIF-8@PDA@QS is weighed into an iodine volumetric flask, and a certain volume of microplastic suspension is transferred therein. The ratio of the concentration of the microplastic suspension to the concentration of the adsorbent is 5 to 10:
1. The oscillator is placed in an air bath constant temperature oscillator and oscillated at an oscillation rate of 180 r / min for 120 min at room temperature.
Citation Information
Cited By
Super-hydrophobic composite filler for bioretention facility as well as preparation method and application of super-hydrophobic composite filler
CN121288790A
A super-hydrophobic composite filler for a bioretention facility and a preparation method and application thereof
CN121288790B